2023
DOI: 10.3389/fonc.2023.1209707
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic mathematical model based on tumor microenvironment-related genes expression for breast cancer patients

Hong Chen,
Shan Wang,
Yuting Zhang
et al.

Abstract: BackgroundTumor microenvironment (TME) status is closely related to breast cancer (BC) prognosis and systemic therapeutic effects. However, to date studies have not considered the interactions of immune and stromal cells at the gene expression level in BC as a whole. Herein, we constructed a predictive model, for adjuvant decision-making, by mining TME molecular expression information related to BC patient prognosis and drug treatment sensitivity.MethodsClinical information and gene expression profiles were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In recent years, the TME has been recognized as having a key role in tumor initiation, progression, metastasis, and immunotherapy response 47 50 . A single-cell analysis showed that SPTBN2 is highly expressed in tumor cells, which suggests that SPTBN2 may promote cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the TME has been recognized as having a key role in tumor initiation, progression, metastasis, and immunotherapy response 47 50 . A single-cell analysis showed that SPTBN2 is highly expressed in tumor cells, which suggests that SPTBN2 may promote cancer.…”
Section: Discussionmentioning
confidence: 99%